Agenda Setting Kampanye Prabowo dalam Memperbaiki Citra Pada Pemilu Tahun 2024 - Hidayah, Nurul Ulhaq; Budiwaspada, Agung Eko; Mansoor, Alvanov Zpalanzani (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2024)
Abstract Agenda setting in political campaigns is a common strategy, including by Prabowo Subianto as presidential candidate number 2 in the 2024 Presidential and Vice-Presidential Election. Prabowo, who has a controversial past, needs to design a strategy to change public perception and increase his electability. One of the most effective ways to dominate voters' votes is to attract support from the younger generation, namely Gen Z and Millennials, through social media and offering relevant visions and missions. This study aims to analyze how the agenda setting strategy carried out by Prabowo Subianto can change his image in the eyes of the public and attract the interest of the younger generation, resulting in an increase in the electability of candidate pair 2 in the 2024 election. The focus of this study is on the agenda setting that is considered the most viral or influential on public opinion. The results of the study show various data that describe the agenda setting strategy implemented by Prabowo's successful team, which succeeded in changing the image and increasing the electability of candidate pair 2.